2021
DOI: 10.3390/ma14164587
|View full text |Cite
|
Sign up to set email alerts
|

Titanium in Cast Cu-Sn Alloys—A Review

Abstract: The article reviews the progress made on bronze alloys processed through various casting techniques, and focuses on enhancements in the microstructural characteristics, hardness, tensile properties, and tribological behaviour of Cu-Sn and Cu-Sn-Ti alloys. Copper and its alloys have found several applications in the fields of automobiles, marine and machine tools specifically for propellers in submarines, bearings, and bushings. It has also been reported that bronze alloys are especially used as an anti-wear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The cladding materials included Cu-Al-Ti-Sn flux-cored wires for preparing copper matrix composite coatings, Cu-Ni-Ti fluxcored wires for preparing the interlayer, and S214 commercial aluminum-bronze wires for comparison with composite coatings in wear resistance. Al and Sn in the welding wires can strengthen the copper matrix, and Ti can react with C in situ to form TiC, which improves the wear resistance of the coatings [33][34][35]. All wires were 1.6 mm in diameter, and the chemical compositions are given in Table 2.…”
Section: Coating Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cladding materials included Cu-Al-Ti-Sn flux-cored wires for preparing copper matrix composite coatings, Cu-Ni-Ti fluxcored wires for preparing the interlayer, and S214 commercial aluminum-bronze wires for comparison with composite coatings in wear resistance. Al and Sn in the welding wires can strengthen the copper matrix, and Ti can react with C in situ to form TiC, which improves the wear resistance of the coatings [33][34][35]. All wires were 1.6 mm in diameter, and the chemical compositions are given in Table 2.…”
Section: Coating Preparationmentioning
confidence: 99%
“…According to the phase diagrams of Cu-Ni and Fe-Ni [34], Ni has a high solid solubility in both Fe and Cu. Therefore, Ni can promote the mixing of Fe and Cu in the molten pool and increase their mutual solubility [36].…”
Section: Eds Spotsmentioning
confidence: 99%
“…As for np-Cu 1 Sn 1 , Sn signals (PDF#04-007-2340) become strong, indicating severe Sn precipitation due to the large density difference. 10 Apart from Cu, CuSn alloy (PDF#04-007-2340) is formed on the np-Cu 1 Sn 1 .…”
mentioning
confidence: 99%
“…Li et al [ 18 ] revealed the microstructural evolution of lamellar-structured high-purity Ni through cold rolling and cryo-rolling. Finally, Manu et al [ 19 ] reviewed the roles of titanium in cast Cu alloys. Their review work summarizes various casting techniques to fabricate bronze alloys, mainly focusing on the microstructures, tensile properties, and tribological characteristics of Cu–Sn and Cu–Sn–Ti alloys [ 19 ].…”
mentioning
confidence: 99%
“…Finally, Manu et al [ 19 ] reviewed the roles of titanium in cast Cu alloys. Their review work summarizes various casting techniques to fabricate bronze alloys, mainly focusing on the microstructures, tensile properties, and tribological characteristics of Cu–Sn and Cu–Sn–Ti alloys [ 19 ]. All these theoretical and experimental works aforementioned in this SI will shed new light on fabricating the non-ferrous materials with high performances.…”
mentioning
confidence: 99%